The Impact of Pandemic Covid-19 on the Performance of Regional Public Hospital Based Approach to Balanced Scorecard in RSUD "X" - Fannidya Hamdani Zeho; Endah Setyowati; Romy Hermawan (Wacana Journal of Social and Humanity Studies, 2020)
The study aims to analyze and identify the impact of the Covid-19 pandemic on the performance of the Regional Public Hospital "X" based on a balanced scorecard. The author analyzes performance using a balanced scorecard measuring instrument. Where the balanced scorecard has four perspectives, namely the perspective of finance, customers, internal business processes, and learning and growth. These perspectives can measure performance comprehensively. The type of research used is descriptive with a qualitative approach. The results show that hospital performance is measured by the perspective on the balanced scorecard, there is a significant impact of the Covid-19 pandemic on performance seen from four perspectives. From a financial perspective it is affected by a decrease in income and the large amount of expenditure. The customer perspective shows a decrease in the number of patients caused by restrictions on admission. The internal perspective of the business process has operational constraints. Meanwhile, the learn and growth perspective experiences an impact due to the high stress experienced by employees.